1989
DOI: 10.1002/1520-6629(198910)17:4<283::aid-jcop2290170402>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A bitter bean: Mental health status and attitudes in chinatown

Abstract: This interview sample survey of adult residents of San Francisco's Chinatown was conducted in an effort to understand the phenomenon of underutilization of mental health services by Chinese Americans and the reasons underlying this phenomenon. Findings revealed that the use rate of mental health services was extremely low, with only 5% of respondents having sought mental health services, suggesting that this ethnic community has not yet seen the gains promised by the community mental health movement. At the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…One potential factor may be knowledge, or lack of knowledge, of available services: it is possible that help-seeking attitudes were influenced by whether or not students in the sample knew about the university's counseling services or other similar services, how to access such services, and whether those services were affordable. Although knowledge about services does not necessarily lead to actual help-seeking behavior, previous studies have shown that lack of knowledge is likely to prevent an individual from seeking services (Bram 1997;Loo et al 1989;Yorgason et al 2008). Therefore, counseling center outreach programs may be more effective if focused not just on reducing mental health stigma or overcoming greater selfconcealment, but also on providing basic information about what services are available and how to access them.…”
Section: Discussionmentioning
confidence: 99%
“…One potential factor may be knowledge, or lack of knowledge, of available services: it is possible that help-seeking attitudes were influenced by whether or not students in the sample knew about the university's counseling services or other similar services, how to access such services, and whether those services were affordable. Although knowledge about services does not necessarily lead to actual help-seeking behavior, previous studies have shown that lack of knowledge is likely to prevent an individual from seeking services (Bram 1997;Loo et al 1989;Yorgason et al 2008). Therefore, counseling center outreach programs may be more effective if focused not just on reducing mental health stigma or overcoming greater selfconcealment, but also on providing basic information about what services are available and how to access them.…”
Section: Discussionmentioning
confidence: 99%
“…In other cultural contexts, even when a person experiences severe psychological struggles, seeking mental health services is not even recognized as an option. Therefore, it seems crucial for service providers to acknowledge and work accordingly in light of the fact that, in some socio-cultural contexts, mental health service utilization is not an established cultural practice (Loo et al 1989) and that service underutilization is not simply due to negative images (e.g., stigma or shame) associated with mental illness or mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial prevalence rates, symptoms of depression often go unrecognized, undiagnosed, and untreated due to patient-and health-care-related barriers and problems in the organization and financing of mental health services for older adults, especially minority elders (Gottlieb, 1991). Studies (Loo, Tong, & True, 1989;Snowden & Cheung, 1990) also suggest that minority elders and immigrants tend to underutilize mental health services, even though the prevalence and types of reported psychological disorders were similar to those in the white population. Depressive symptoms do not tend to remit spontaneously in older adults (Allen & Blazer, 1991), and undiagnosed and untreated depression in late life usually cause tremendous distress for older adults, their families, and society.…”
Section: Literature Reviewmentioning
confidence: 99%